A concise test of rational consumer search - Chloe Lee; Maria José Luengo-Prado; Bent E. Sørensen (Federal Reserve Bank of Boston, 2018)
A simple model of time allocation between work and price-search predicts that consumers spend relatively more time searching for better prices for goods of which they consume relatively more. Using scanner data, we confirm empirically that consumers pay lower (higher) prices for goods that they buy more (less) of than other consumers. Our results are conservative, because we compare goods that are defined as narrowly as possible by UPC codes, and provide a lower bound for the savings obtained from bargain hunting.
Keywords: E21; D12; 330; consumption; consumer search; time use